Host plant preference and life cycle of whitefly (Bemisia Tabaci, Gennadius), its toxicity and populations susceptibility against selected insecticides / Hazmi Awang Damit - Awang Damit, Hazmi (2008)
The sweetpotato whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) is a tiny, soft-bodied insect with sucking type mouthpart and is not a true fly. It is a serious insect pest and has an extremely wide range of hosts including edible, ornamental crops and weeds. In this study, five main areas were given emphasis namely, host plant preference, life cycle, fecundity, toxicology and resistance level in the populations of B. tabaci collected from fields. The study of host plant preferences on both multi-choice and no-choice tests found that the two most preferred host plants of B. tabaci were brinjal (Solanum melongena) and tobacco (Nicotiana tabacum).